2019
DOI: 10.1038/s41598-019-47163-y
|View full text |Cite
|
Sign up to set email alerts
|

White LED Light Exposure Inhibits the Development and Xanthophore Pigmentation of Zebrafish Embryo

Abstract: Circadian rhythm in all living organisms is disturbed continuously by artificial light sources and artificial lighting has become a hazard for public health. Circadian rhythm of melatonin maintains high levels of melatonin during the night and low levels during the day. N-acetyltransferase (arylalkylamine N-acetyltransferase, AANAT) is one of the four enzymes required for melatonin synthesis and mtnr1ba is a melatonin receptor-encoding mRNA that is expressed widely in the embryonic brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Photoperiod (light-dark) is an external environmental factor that induces photoreceptive tools to adapt to photoreceptor sensitivity [49]. Aanat2 and mtnr1ba expression support melatonin production and photoperiod marker in vertebrates [13,44]. In our study, mtnr1ba and aanat2 were expressed in all wavelength treatments in response to the 14:10 LD time treatment given to all wavelength treatments.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Photoperiod (light-dark) is an external environmental factor that induces photoreceptive tools to adapt to photoreceptor sensitivity [49]. Aanat2 and mtnr1ba expression support melatonin production and photoperiod marker in vertebrates [13,44]. In our study, mtnr1ba and aanat2 were expressed in all wavelength treatments in response to the 14:10 LD time treatment given to all wavelength treatments.…”
Section: Discussionmentioning
confidence: 61%
“…Light might play a significant role in embryogenesis; blue light wavelengths ranging from 400 to 500 nm (near-ultraviolet) are suspected to be potentially harmful to cells (gametes and embryos). Some previous studies have concluded that blue light is most damaging, with damage causing as much as 100 % mortality in 72 hpf zebrafish embryos [44].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Zebrafish have become a crucial model organism for studying hypoxic conditions due to their external fertilization, small size, rapid development, high reproductive output, and transparent larval bodies, facilitating easy observation ( Üstündağ et al ., 2019 ). Under OD conditions, oxygen diffusion from the gills to the blood is impaired, affecting respiratory efficiency ( Pelster, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Larvae at the age of 3 dpf were followed until they reached 9 dpf for subsequent measurements, in line with the methodologies of larvae aged 3 dpf and were monitored until they reached 9 dpf for measurement ( Avdesh et al ., 2012 ). Larvae aged 3 dpf were observed until they reached 9 dpf for measurement ( Üstündağ et al ., 2019 ). All protocols for handling and care of these laboratory animals were in strict compliance with the established ethical guidelines for laboratory animal welfare.…”
Section: Methodsmentioning
confidence: 99%